The optimum matching control and dynamic analysis for air suspension of multi-axle vehicles with anti-roll hydraulically interconnected system. (May 2020) - Li, Hongxue; Li, Shiwu; Sun, Wencai; Wang, Linhong; Lv, Dongye
Highlights: Hydraulic controllers are modelled and coupling multi-axle vehicle models are established based on co-simulation. Optimum matching controller is obtained by analyzing the stability of vehicle. A fuzzy logic controller as the second auxiliary control is designed to further improve performance of vehicle suspension. Abstract: The control of suspension has been extensively studied and practically utilized in numerous fields of the automotive industry. However, few studies have been conducted on the suspension performance of multi-axle vehicles with an anti-roll hydraulically interconnected system control. In order to solve this problem, the present study is focused on the roll-resistance performance and optimum matching of articulated vehicles equipped with anti-roll hydraulic interconnected control suspension. Three hydraulic interconnected control systems for single-axle, dual-axle and tri-axle suspension of semitrailers are firstly modelled and verified in AMESim, and then seven coupling vehicle models are established by co-simulation method in AMESim, MATLAB/Simulink and Trucksim. Dynamic simulation analysis shows that D23 and D123 have great application value as the optimum strategy considering the engineering cost and anti-roll capacity. Subsequently, a fuzzy controller is proposed for the problem of insufficient roll resistance of D23. The results show that designed controller can further effectively improve the handling stability of vehicle.